Birth – Strategies of Description in “Efemeros” by Bazyli Rudomicz - Szafrańska, Monika (Melusine. Old Literature and Culture, 2026)
Article “Birth - Strategies of Description in Efemeros by Bazyli Rudomicz” is an attempt to analyze ways of describing a seventeenth-century memoirist. The author draws attention to what a Rudomicz dealt with and interested in, distinguishing individual strategies for creating notes in his diary. The memoirist presents himself as a person who creates various discourses, depending on the way he looked at a given situation. Rudomicz was involved in individual roles. He looked at events as not only a observer, but also as a father, doctor or as a burgher seeking sensation and novelty. He described what was most important or new to him, which gave him the opportunity to observe significant people. Completly differently he described which seemed universal in his opinion, or something he was accustomed about.